2015
DOI: 10.1089/neu.2014.3715
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neurochemistry in Former Professional Soccer Players without a History of Concussion

Abstract: Soccer is played by more than 250 million people worldwide. Repeatedly heading the ball may place soccer players at high risk for repetitive subconcussive head impacts (RSHI). This study evaluates the long-term effects of RSHI on neurochemistry in athletes without a history of clinically diagnosed concussion, but with a high exposure to RSHI. Eleven former professional soccer players (mean age 52.0±6.8 years) and a comparison cohort of 14 age- and gender-matched, former non-contact sport athletes (mean age 46.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 44 publications
3
143
3
2
Order By: Relevance
“…74 In a study of 11 former professional soccer players, MRS revealed a significant increase in choline (a marker for cellular proliferation and tissue damage) and myoinositol (a glial activation marker) compared with age-matched controls. 68 No neurocognitive deficits were reported in this study group. Another series, which compared 10 concussed athletes with 10 nonconcussed athletes in both acute and chronic injury phases, demonstrated neurochemical impairment in the prefrontal and motor (M1) cortex, particularly a chronic pathological increase in creatine and myoinositol in the M1 cortex.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 51%
“…74 In a study of 11 former professional soccer players, MRS revealed a significant increase in choline (a marker for cellular proliferation and tissue damage) and myoinositol (a glial activation marker) compared with age-matched controls. 68 No neurocognitive deficits were reported in this study group. Another series, which compared 10 concussed athletes with 10 nonconcussed athletes in both acute and chronic injury phases, demonstrated neurochemical impairment in the prefrontal and motor (M1) cortex, particularly a chronic pathological increase in creatine and myoinositol in the M1 cortex.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 51%
“…Relative to healthy controls, chronically elevated levels of neuroinflammation, as detected via PET scan, can persists both years after a single remote TBI as well as years after exposure to repetitive neurotrauama, even in the absence of a clinically evident TBI [61][62][63][64] . Notably, one study that also investigated neuronal white matter integrity found that levels of microglial activations correlated with structural changes in the brain 63 .…”
Section: Immunological Perspectives Of Tbi Sequelaementioning
confidence: 99%
“…However, recent evidence suggests that RHI, especially if they occur in close proximity in time, may lead to structural and functional brain alterations and clinical impairment even if there are no acute symptoms [2][3][4][5] (for review see Koerte et al 6 ). More severe effects are expected when a child with insufficient neck strength attempts to head a ball 7 .…”
Section: Introductionmentioning
confidence: 99%